Major Crop Species Show Differential Balance between Root Morphological and Physiological Responses to Variable Phosphorus Supply - Lyu, Yang; Tang, Hongliang; Li, Haigang; Zhang, Fusuo; Rengel, Zed; Whalley, William R.; Shen, Jianbo (Frontiers in Plant Science, 2016)
The relationship between root morphological and physiological responses to variable P supply in different plant species is poorly understood. We compared root morphological and physiological responses to P supply in seven crop species (Zea mays, Triticum aestivum, Brassica napus, Lupinus albus, Glycine max, Vicia faba, Cicer arietinum) treated with or without 100 mg P kg−1 in two soils (acidic and calcareous). Phosphorus deficiency decreased root length more in fibrous root species (Zea mays, Triticum aestivum, Brassica napus) than legumes. Zea mays and Triticum aestivum had higher root/shoot biomass ratio and Brassica napus had higher specific root length compared to legumes, whereas legumes (except soybean) had higher carboxylate exudation than fibrous root species. Lupinus albus exhibited the highest P-acquisition efficiency due to high exudation of carboxylates and acid phosphatases. Lupinus albus and Cicer arietinum depended mostly on root exudation (i.e. physiological response) to enhance P acquisition, whereas Zea mays, Triticum aestivum and Brassica napus had higher root morphology dependence, with Glycine max and Vicia faba in between. Principal component analysis using six morphological and six physiological responses identified root size and diameter as the most important morphological traits, whereas important physiological responses included carboxylate exudation, and P-acquisition and P-utilization efficiency followed by rhizosphere soil pH and acid phosphatase activity. In conclusion, plant species can be grouped on the basis of their response to soil P being primarily via root architectural or exudation plasticity, suggesting a potential benefit of crop-specific root-trait-based management to cope with variable soil P supply in sustainable grain production.